O olhar, a menina dos olhos, única e total : compreensão fenomenológica do Programa Meninas dos Olhos de Deus e das dimensões da Exploração Sexual Comercial de Crianças e Adolescentes em interface com a educação - Fernandes, Raquel Martins (2012)
Commercial sexual exploitation of children and teenagers in Brazil and all around the world disquiets many social groups and researchers from different areas. This doctoral research in Education (inscribed in the research line Social movements, politics and popular education, from the Education Institute, at Universidade Federal de Mato Grosso) aims to study such reality. We investigate national and international projects with relative institutional visibility, which promote educational processes with children and teenagers victimized by, or vulnerable to, commercial sexual exploitation, specially the program Apple of God´s Eyes (Global Mobilization – NGO). The main objective of this research was to understand the meaning of education in the testimonials by the leaders of the program Apple of God´s Eyes, as well as its relation to the corps propre dimension in Maurice Merleau-Ponty´s speech, so as to unveil issues related to the commercial sexual exploitation of children and teenagers. To do so, we have made a qualitative research with phenomenological foundations, based on MerleauPonty, and a systematic bibliographic review in virtual environments on commercial sexual exploitation of children and teenagers and related themes, based on the following descriptors: commercial sexual exploitation, sexual violence against children and teenagers, sexual abuse against children and teenagers, sexual traffic of children and teenagers, child prostitution. We have also researched publications by the program Apple of God´s Eyes in its official site, magazines, journals and interviews with 25 leaders. We have also researched papers on Merleau-Ponty and three doctoral theses about the author. This intellectual route permitted us to choose and employ more adequate categories to understand such phenomenon. We have identified, throughout the process of focusing and defocusing images, singularities in this phenomenon, which could only be seen when we changed the angle of its perception and its reference system. Therefore, these images could not be previously understood as static or extinguishable, due to their polysemy and the multidimensional perception of the commercial sexual exploitation of children and teenagers. Regarding the concept of education in the program Apple of God´s Eyes, we could see a notion of love-based education, which mutually dignifies the subject in their singularity, personality and integrality. We also realized that the idea of otherness is part of the process of their leaders´ identity construction. It was concluded that the problem of commercial sexual exploitation of children and teenagers is full of multidimensionality, which is not restricted to the violence of socioeconomical oppression and disregard of the human condition. It implies the production of a symbolic system that generates cultural stigmatization, impacting on all the being´s dimensions, from local and personal to political and planetary implications.